2017
DOI: 10.1111/maps.12820
|View full text |Cite
|
Sign up to set email alerts
|

Origin of mass‐independent oxygen isotope variation among ureilites: Clues from chondrites and primitive achondrites

Abstract: Ureilite meteorites are abundant, carbon‐rich, primitive achondrites made of coarse‐grained, equilibrated olivine and pyroxene (usually pigeonite). They probably sample the baked, heterogeneous, melt‐depleted mantle of a large, once‐chondritic parent body that was broken up catastrophically while still young and hot. Heterogeneity in the parent body is inferred from a considerable “slope‐1” variation from one meteorite to another in oxygen isotopes (−2.5‰ < Δ17O < −0.2‰), which correlates with both molar FeO/M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 82 publications
(296 reference statements)
1
21
1
Order By: Relevance
“…; Sanders et al. ). The heterogeneity is indicated by the wide variation in bulk composition, Fo content of olivine, and oxygen isotopes among the various ureilite meteorites (e.g., Clayton and Mayeda ; Downes et al.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…; Sanders et al. ). The heterogeneity is indicated by the wide variation in bulk composition, Fo content of olivine, and oxygen isotopes among the various ureilite meteorites (e.g., Clayton and Mayeda ; Downes et al.…”
Section: Introductionmentioning
confidence: 98%
“…Considering the final steps of the UPB history, Goodrich et al (2004) suggested that the UPB broke up early in the solar system, i.e., about 5 Ma after CAI formation, and reassembled as one or more daughter bodies (ureilite daughter body, UDB). The known ureilites are derived most likely from one of the heterogeneous brecciated UDBs (Downes et al 2008;Herrin et al 2010a;Warren 2012;Goodrich et al 2015;Sanders et al 2017). The heterogeneity is indicated by the wide variation in bulk composition, Fo content of olivine, and oxygen isotopes among the various ureilite meteorites (e.g., Clayton and Mayeda 1988;Downes et al 2008;Warren 2012).…”
Section: Introductionmentioning
confidence: 99%
“…This might have occurred within the ureilite parent body, which initially could be rich in volatile components (Sanders et al. ).…”
Section: Resultsmentioning
confidence: 99%
“…Experiments have shown that various H 2 -CO-CO 2 -H 2 O gas mixtures are active reduction agents and are able to reduce iron from oxides to a metal (Kemppainen et al 2012) at temperatures assumed for ureilites' petrogenetic processes. This might have occurred within the ureilite parent body, which initially could be rich in volatile components (Sanders et al 2017).…”
Section: Dhofar 1285mentioning
confidence: 99%
See 1 more Smart Citation